Eficiência de solo vegetado com bambu barriga de Buda (Bambusa tuldoides cv. ventricosa), família Poaceae, na remoção do hormônio 17α-etinilestradiol de um efluente sanitário - Barrero, Lullyane de Queiroz Rodrigues (2017)
The endocrine disrupting compound 17 α-ethinylestradiol (EE2), present in female contraceptives, after consumption, is eliminated by urine and goes into the sewer system. Conventional sewage treatment methods cannot properly remove such chemical which is then carried into the receiving bodies, where they are capable of mimicking, antagonizing or negatively altering steroids levels of various aquatic organisms. The purpose of this study was to evaluate the usage potential of soil covered with Buddhas's Belly bamboo (Bambusa tuldoides cv. ventricosa) in removing EE2 from sewage. For this, 760 mL of sanitary sewage containing 2 mg EE2/L; 2.5 mg EE2/L; 3 mg EE2/L and 3.5 mg EE2/L, were applied in 10L plastic pots, with grown Buddha's Belly bamboo plants. The drained fluid from each pot was collected, measured and subjected to EE2 concentration analysis. The efficiency of EE2 load (concentration times volume) removal was calculated and the treatments were compared. The efficiency of EE2 removal was 80.22%; 87.44%; 89.65% and 95.33% respectively for sewage with EE2 concentrations of 2 mg/L; 2.5 mg/L; 3 mg/L and 3.5 mg/L. The efficiency of EE2 removal by soil covered with bamboo increased as the concentration of hormone increased.